1997
DOI: 10.1002/(sici)1097-0339(199701)16:1<87::aid-dc19>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Intralaboratory quality assurance in cervical/vaginal cytology: Evaluation of intercytologist diagnostic reproducibility

Abstract: Diagnostic reproducibility and accuracy in evaluating cervical/vaginal smears were the focus of this study concerning intralaboratory quality control. A set of 120 cytological samples was evaluated by 15 cytopathologists whose experience ranged from 3–29 yr. The study report form was based on the 1988 Bethesda System. Intercytologist reproducibility (with respect to sample adequacy, epithelial cell abnormalities, and presence of cellular changes associated with HPV, Human Papilloma virus) was evaluated using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
0
14
0
2
Order By: Relevance
“…Similar to these results, a Brazilian study found that the agreement between conventional cytology and LBC was highest in the NILM category. 28 The authors further noted that this influenced the agreement rate, as the majority of cervical smears were negative. In comparison, the proportion of samples that showed abnormal cytology exceeded 60% for both preparation methods in the current study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar to these results, a Brazilian study found that the agreement between conventional cytology and LBC was highest in the NILM category. 28 The authors further noted that this influenced the agreement rate, as the majority of cervical smears were negative. In comparison, the proportion of samples that showed abnormal cytology exceeded 60% for both preparation methods in the current study.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have also documented below-excellent agreement for epithelial abnormalities when comparing conventional cytology to LBC preparations. 27,28 Factors that influence agreement include the method employed to collect the smear, variations in cellular material between the conventional and LBC samples and the level of experience of the cytotechnologists in interpreting the smears. 29,30,31,32,33,34 …”
Section: Discussionmentioning
confidence: 99%
“…The interobserver reliability for cervical cytology and histology generally has been assessed as moderate. [22][23][24][25] Two studies of cervical cytology showed that agreement was similar whether liquid-based or conventional cytology preparations were used. 26,27 Few studies have evaluated the reliability of anal specimen reporting.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the participants were unable to differentiate between ASCUS and LSIL based on nuclear enlargement criteria, a finding which may implicate nuclear-enlargement determination as contributing to the well-documented poor reproducibility of the ASCUS diagnosis. [4][5][6][8][9][10]19 Furthermore, because ASCUS and LSIL are the major contributors to ASC and SIL, respectively, the difficulty in differentiating between ASCUS and LSIL is a likely explanation for the wide variation of ASC to SIL ratios between laboratories 1,3 and between cytotechnologists and pathologists, even when they practice at the same institution. [20][21][22][23][24][25][26][27] Previous studies have suggested that the variability among pathologists in the classification of squamous abnormalities may be related to differences in both diagnostic thresholds as well as in diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%